De Tocqueville - Welch, Cheryl B. (Oxford ; New York : Oxford University Press, 2001)
"Welch argues that Tocqueville's major themes tap into deep anxieties about democratic practices and that his writings help us to identify some of the major fault lines in democracy at the turn of the new century. Beginning with consideration of Tocqueville's distinctiveness against the historical background and intellectual context of his time, Welch goes on to trace the development of his thought on democracy and revolution, freedom and history, slavery, religion, and gender, including chapters dealing with his major writings on the United States and France. The final chapter then explores Tocqueville's historical legacy and his contemporary significance, illuminating the reasons why this displaced nineteenth-century aristocrat has become one of the most topical and debated figures in contemporary political and social theory."--BOOK JACKET.
Machine derived contents note: 1. Tocqueville in his time -- 2. The shape of democracy itself -- 3. The natural destiny of a people -- 4. The secrets of the heart -- 5. Tocqueville in our time.
Includes bibliographical references (p. [263]-273) and index.
Keywords: Tocqueville, Alexis de, -- 1805-1859.; Politieke filosofie